2021
DOI: 10.3390/app112210543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging and Moisture Damage on Fatigue Cracking Properties in Asphalt Mixtures

Abstract: Recently, damage to asphalt pavements in South Korea has increased because of direct and indirect factors caused by abnormal climatic changes, such as torrential rains, prolonged heatwaves in summer, and heavy snowfall in winter. Additionally, the use of medium and heavy vehicles is also a contributing factor. Therefore, an experimental procedure to study the moisture damage and fracture properties of asphalt pavements considering the recent changes in precipitation properties, deterioration of road pavement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The corresponding data are presented as semi-log and log-log graphs in Figure 5. The semilog and log-log graphs reveal the behavior at low and high temperatures, respectively [18]. Figure 5 illustrates the DMT results for the HMA in different stages of aging, indicating that the dynamic modulus increased with age.…”
Section: Dynamic Modulusmentioning
confidence: 96%
See 2 more Smart Citations
“…The corresponding data are presented as semi-log and log-log graphs in Figure 5. The semilog and log-log graphs reveal the behavior at low and high temperatures, respectively [18]. Figure 5 illustrates the DMT results for the HMA in different stages of aging, indicating that the dynamic modulus increased with age.…”
Section: Dynamic Modulusmentioning
confidence: 96%
“…The corresponding data are presented as semi-log and log-log graphs in Figure 5. The semilog and log-log graphs reveal the behavior at low and high temperatures, respectively [18]. Figure 5…”
Section: Dynamic Modulusmentioning
confidence: 97%
See 1 more Smart Citation
“…The fatigue life increases when the asphalt content increases. Yang et al, (2021), [3] evaluated the effect moisture damage and ageing on fatigue cracking of asphalt concrete. It was observed that the material properties of hot mix asphalt mixtures changed after practicing aging and moisture damage.…”
Section: Introductionmentioning
confidence: 99%
“…For the specimens sampled on site, the influence of aging and reducing the performance and failure strength of asphalt mixture relative to the control and original state is inevitable. Some researchers have studied the effect of aging of asphalt mixtures, bituminous materials, the effects of mixtures made of RAP and aged materials [ 9 , 10 , 11 , 12 ]. Among many experimental methods, triaxial tests are widely used because they can accurately simulate mechanical conditions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%